"Neither too much nor too little" France, the USSR and the Helsinki CSCE. Issue 1 (2nd January 2018) - Badalassi, Nicolas
Abstract: In the early 1970s, the Conference on Security and Cooperation in Europe (CSCE) was the cornerstone of French foreign policy regarding East-West relations. It was considered by Paris as the best way to maintain dialogue with Moscow as well as an instrument to reach the Gaullist goal of overcoming the European status quo. This double objective explains why the French adopted an ambiguous attitude during the CSCE: even though their goal was to challenge the Brezhnev doctrine and initiate a process to meet the aspirations of peoples under Soviet domination, they knew that this would be a lengthy process. For them, it was necessary to avoid provoking the Soviets by putting forward expressively liberal proposals. The French leaders of the 1970s saw the CSCE as the multilateral prolongation of the Gaullist policy of ' détente, entente, cooperation '.